The Strategic Choices of Companies from the Perspective of the Theory of Structuration - Urbanowska-Sojkin, Elżbieta (Studia Oeconomica Posnaniensia, 2017)
The subject matter of the article is the strategic choice. The author’s attention has been focused on the choices understood in a broad sense. The conditions of the functioning of companies, commonly referred to as conditions of unbalance, require other ways of describing and explaining than the ones applied so far, thus stimulation of the search for such theoretical approaches would allow for a deeper insight into the strategic choice. The aim of the article is to determine whether the theory of structuration could be applied in the explanation of strategic choices of companies.